2008
DOI: 10.2337/db07-1186
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Adipocyte Insulin Resistance in the Pathogenesis of Obesity-Related Elevations in Endocannabinoids

Abstract: OBJECTIVE-Obesity is associated with an overactive endocannabinoid (EC) system. The mechanisms responsible for increased ECs in obese individuals are poorly understood. Therefore, we examined the role of adipocyte insulin resistance in intracellular EC metabolism.METHODS-We used 3T3-L1 adipocytes and diet-induced obese (DIO) mice to examine the role of obesity and insulin resistance in the regulation and/or dysregulation of intracellular ECs.RESULTS-For the first time, we provide evidence that insulin is a maj… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
73
0
4

Year Published

2008
2008
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 93 publications
(86 citation statements)
references
References 29 publications
(26 reference statements)
9
73
0
4
Order By: Relevance
“…[14][15][16]18,21 It is, however, rather surprising in light of the findings by others showing that HF diets given to mice cause dysregulation of the ECS, either via alterations in the expression of CB 1 receptors, via alterations in the levels of endogenous ligands, or both. 17,[40][41][42] Also the fatty acid composition of dietary fat may influence endocannabinoid action. 43 For example, the presence or absence of n-3 PUFAs in the diet affects endocannabinoid levels in the brain, as shown by Berger et al 44 and Watanabe et al 45 Batetta et al 46 recently found that dietary n-3 PUFAs can reduce inflammatory markers and liver triglyceride levels, and these effects were associated with lower levels of endocannabinoid ligands in peripheral organs.…”
Section: Discussionmentioning
confidence: 99%
“…[14][15][16]18,21 It is, however, rather surprising in light of the findings by others showing that HF diets given to mice cause dysregulation of the ECS, either via alterations in the expression of CB 1 receptors, via alterations in the levels of endogenous ligands, or both. 17,[40][41][42] Also the fatty acid composition of dietary fat may influence endocannabinoid action. 43 For example, the presence or absence of n-3 PUFAs in the diet affects endocannabinoid levels in the brain, as shown by Berger et al 44 and Watanabe et al 45 Batetta et al 46 recently found that dietary n-3 PUFAs can reduce inflammatory markers and liver triglyceride levels, and these effects were associated with lower levels of endocannabinoid ligands in peripheral organs.…”
Section: Discussionmentioning
confidence: 99%
“…Previous data suggest that both glucose and insulin may affect EC biosynthesis and degradation in isolated cells (12,16,17). Therefore, in this study, we aimed at gaining direct evidence, in intervention studies carried out in two different cohorts of volunteers, of potential effects of either oral glucose load or insulin infusion on plasma EC levels.…”
Section: Discussionmentioning
confidence: 99%
“…Among the possible causes of the peripheral dysregulation of the EC system, the lack of negative control by insulin on EC levels has been suggested by previous studies (12,16,17). In particular, experiments in isolated cells have shown that conditions mimicking high glucose and/or insulin resistance can enhance EC levels in models of adipocytes and pancreatic b-cells (12,17).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Az inzulin, D'Eon és munkatársai kutatásai alapján, csökkenti az endokannabinoidtermelést, és serkenti azok lebomlását [17]. Amikor az adipocyták inzulin iránti szenzitivitása csökken, újra megemelkedhet az endokannabinoidszint.…”
Section: A Kannabidiol Jelentősége Obesitásbanunclassified